IMPROVING THE WRITING SKILLS OF COMPLEX PROCEDURAL TEXTS WITH SCRAMBLE METHOD FOR STUDENTS OF CLASS VII-A SMP NEGERI 25 MAKASSAR - Reskiani Saparuddin; Jumriati; Erniati; Dwi Syukriady (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This study aims to improve the quality of the learning process and the ability to write complex procedure texts using the Scramble method in class VII-A students of UPT SPF SMP Negeri 25 Makassar. This type of research is classroom action research (CAR) which is carried out in two cycles, namely cycle I and cycle II, using four stages, namely planning, implementation, observation, and reflection. The subjects of this study were 30 class VII-A students of UPT SPF SMP Negeri 25 Makassar, 16 male students and 14 female students. Data collection techniques are test techniques and non-test techniques. Based on the results of the study, it shows that students' complex procedure text writing skills have increased, as evidenced by the average score in cycle I of (44.43%) increasing to (82.76%) in cycle II. And students experienced an increase in changes in activity and attitude when the Scramble learning media was applied in cycle I learning 70% increased in cycle II to 90%, students who paid attention to the teacher's explanation by 76.66% increased in cycle II by 83.33%, students who actively asked questions by 16.66% increased to 56.66%, students who were not noisy during learning by 40% increased to 76.66% in cycle II, and students who were calm when doing assignments by 86.66% and increased in cycle II by 90%. It can be concluded that learning the skills of writing complex procedural texts using the Scramble method has increased